Escuela de Arte Escénico - Cerdas Bokhan, Dora (Editorial Universidad Nacional (EUNA), 2014)
This book collects the artistic and academic life of ten women and men who have stood out not only in the teaching field at the Center for Research, Teaching and Artistic Extension (CIDEA), but also in the national and international artistic sphere. They, like many other theater artists at heart, have contributed their expertise and life experiences to the artistic environment and for the School of Scenic Art it is a pleasure to demonstrate their artistic and teaching career in this book.